Level of depression, anxiety and stress experienced by student members of armed uniform body at UiTM Perlis Branch / Khor Poy Hua, Muhamad Hairiss Ishak and Lim Khong Chiu - Khor, Poy Hua; Ishak, Muhamad Hairiss; Lim, Khong Chiu (Universiti Teknologi MARA, Negeri Sembilan, 2020)
This study evaluates the depression, anxiety, and stress level among student members of armed uniform body at Universiti Teknologi MARA Perlis Branch. Universiti Teknologi MARA Perlis Branch offered 15 co-curriculum activities included SUKSIS, Komander Kesatria, Bomba, and Angkatan Pertahanan Awam Malaysia. Unfortunately, in the selection system of co-curriculum activities, some students did not have the opportunity to select curriculum activities of their choice and interest. Questionnaire developed by Lovibond and Lovibond's (1995) entitled Depression, Anxiety, and Stress Scale (DASS-21) was issued to 120 student members of SUKSIS, Komander Kesatria, Bomba, and Angkatan Pertahanan Awam Malaysia. In terms of the level of mental health, the student members of SUKSIS and Komander Kesatria suffered mild level of depression, while members of Bomba and Angkatan Pertahanan Awam Malaysia experienced normal level of depression. In relation to anxiety level, members of Suksis and Komander Kesatria suffered moderate level of anxiety, while members of Bomba and Angkatan Pertahanan Awam Malaysia experienced mild level of anxiety. Although the members of Komander Kesatria, Bomba and Angkatan Pertahanan Awam Malaysia experienced normal level of stress, the members of SUKSIS armed uniform body are mildly stressed. These findings provide an insight on mental health among students of tertiary education which is a very serious health issue that demands further exploration for development of effective co-curriculum activities. Hopefully, future researchers could relate this health issue with studies on other populations and demographic characteristics.